Management Guidance and Counseling in School - Heppi Sasmita; Neviyarni Neviyarni; Riska Ahmad; Yarmis Syukur (Pamomong: Journal of Islamic Educational Counseling, 2021)
Management of guidance and counseling in schools is an activity that is carried out within a certain period of time. In order for guidance and counseling services to be carried out effectively and efficiently, in its implementation, guidance and counseling management must be carried out properly. Changes that occur in the behavior of students at school certainly provide an illustration for BK teachers to carry out various service activities, where one form of service which is at the same time the spearhead of all guidance activities is counseling activities. The provision of ongoing guidance and counseling services to students shows that the counselor profession is dynamic. The ability of guidance and counseling teachers to anticipate and choose strategies in accordance with the demands of these needs and developments will be a powerful ammunition to be able to deal with the various dynamics and changes faced For this reason, an understanding of some of the roles of guidance and counseling teachers (counselors) needs to be considered well and the success in the implementation of guidance and counseling can be seen from how the counselor is able to manage each existing service so that the counselor at school can function properly according to the educational goals that have been planned. previously in the school environment.